Не на острове Буяне...: [сказки] / А. А. Усачев ; худ. А. М. Елисеев - Усачев Андрей Алексеевич (Детские классики, 2009)
Экземпляры: ДО мл.аб. (2011) / Инвентарный номер: 46976 / Цена: / Авт.знак: У 74 / ББК: 84